Healthcare for all: scopes and challenges in Indian scenario - Barman, Dipayan Deb; Mohesh, M. I. Glad (International Journal Of Community Medicine And Public Health, 2021)
Health for all may have become a reality in many developed countries but developing economies are still striving hard to achieve that long cherished dream for their people. India as a developing country and as one of the fastest growing economies is also working hard to achieve health for all. There are problems which continue to grapple the Indian health sector services. India has successfully launched various health programs in the past few decades and has achieved success in improving on a few major issues such as maternal and child mortality. India has been declared polio infection free nation by World health organization in February 2012. There is tremendous potential for India to reorganize its health care sector through participation of both public and private sector and developing a competent and trained workforce. In order to enable the country to grow in all parameters it is important that health for all citizens must be ensured and by doing this India will be able to have a healthy population which will be productive and will therefore effectively contribute to the economic growth of the nation.